The Influence of Work Environment and Job Satisfaction on Employee Performance - Sembiring, Emiya Jola Panesia; Firdausiah, Rr. Ayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effects of work environment and job satisfaction on employee performance at Tajinan Health Center, with the objective of providing insights for improving human resource management practices and organizational productivity in public health service institutions. Design/Methodology/Approach – This study employs an explanatory research design with a quantitative approach. Data were collected through Likert-scale questionnaires distributed to all 42 employees of Tajinan Health Center using a saturated sampling technique. The collected data were analyzed using SPSS software to examine the relationships among work environment, job satisfaction, and employee performance. Findings – The results indicate that the work environment has a positive and significant effect on employee performance. Job satisfaction also has a positive and significant effect on employee performance. These findings demonstrate that supportive working conditions and higher levels of employee satisfaction play important roles in improving performance within healthcare service organizations. Originality or Value: This study provides value by analyzing the combined effect of work environment and job satisfaction on employee performance within a real public health setting. The focus on a specific health center offers context based insights that are rarely explored in similar research. The findings contribute useful guidance for improving employee performance and advancing organizational effectiveness in public health institutions.